Molecular dissociation in presence of a catalyst : II. The bond breaking role of the transition from virtual to localized states - Ruderman, Andrés (2016)
Fil: Ruderman, Andrés. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía, Física y Computación; Argentina.